Advances in pharmacology. Volume 44 - August, J. Thomas; ScienceDirect eBooks (San Diego : Academic Press, 1998)
Each volume of Advances in Pharmacology provides a rich collection of reviews on timely topics. Emphasis is placed on the molecular bases of drug action, both applied and experimental.
Drug Therapy: The Impact of Managed Care; The Role of Phosphodiesterase Enzymes in Allergy and Asthma; Modulating Protein Kinase C Signal Transduction; Preventive Role of Renal Kallikrein-Kinin System in the Early Phase of Hypertension and Development of New Antihypertensive Drugs; The Multienzyme PDE4 Cyclic Adenosine Monophosphate-Specific Phosphodiesterase Family: lntracellular Targeting, Regulation, and Selective Inhibition by Compounds Exerting Anti-inflammatory and Antidepressant Actions; Clinical Pharmacology of Systemic Antifungal Agents: A Comprehensive Review of Agents in Clinical Use, Current Investigational Compounds, and Putative Targets for Antifungal Drug Development.
Includes bibliographical references and index.
Print version record.
Elsevier
Keywords: Pharmacology; Therapeutics; MEDICAL -- Drug Guides; MEDICAL -- Nursing -- Pharmacology; MEDICAL -- Pharmacology; MEDICAL -- Pharmacy; Pharmacology; Therapeutics; Electronic books